If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 5(5) = 79 Multiply 5 * 5 6x + 25 = 79 Reorder the terms: 25 + 6x = 79 Solving 25 + 6x = 79 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25' to each side of the equation. 25 + -25 + 6x = 79 + -25 Combine like terms: 25 + -25 = 0 0 + 6x = 79 + -25 6x = 79 + -25 Combine like terms: 79 + -25 = 54 6x = 54 Divide each side by '6'. x = 9 Simplifying x = 9
| 6(9)+5y=79 | | Log[12](x-4)=1-log[12]x | | 3-2x=4y-2 | | 0.6=1x+y | | h+7=70-8h | | 0.6=600000x+y | | 12c-7=10c | | 4y+3(-4)=-12 | | 7a-11=2a+4 | | 5x-4(2)=17 | | 5(-3)-4y=17 | | 240=(x+5)(3x+9) | | 2x^2+40x-600=0 | | B+0,5= | | 1n+2(1n-1)+3n=28 | | ln(x)-ln(3)=19 | | 6m+16n= | | x^3+4x-9x^2+120=0 | | 3k-10=k+2 | | 6r-1+6r+3=17 | | z^3+3iz-i-3=0 | | -10y=12 | | -1-5/7-(-2)=-6/9 | | ln(x)+ln(3)=19 | | (X+2)(X+3)=30 | | L^2+6L-160=0 | | 3x+5=8x-13 | | 3y-5x=43 | | abs(z+4)=3*abs(z-4) | | 16+9t=22 | | 2x-8+3x+21=3 | | 16a-9a+uf= |